LEGAL REGULATION OF ARTIFICIAL INTELLIGENCE APPLICATION IN ANTI-MONEY LAUNDERING: ANALYSIS OF INTERNATIONAL EXPERIENCE - Banakh, Serhiy; Holota, Nataliia (Актуальні проблеми правознавства, 2025)
The article presents a comprehensive examination of the legal aspects of artificial intelligence (AI) applications in anti-money laundering (AML) and counter-terrorism financing (CTF), drawing on an analysis of international experiences in legal regulation. Special attention is paid to the transformation of public perception of the problem following high-profile information leaks - the Panama Papers (2016) and Paradise Papers (2017), which became catalysts for the transition from relative tolerance of asset concealment schemes to active international counteraction to financial crimes. It has been proven that traditional financial monitoring methods are unable to effectively process millions of daily transactions, which necessitates the implementation of cutting-edge AI technologies, including machine learning algorithms (MLA), deep neural networks, and predictive analytics tools. The legal nature of AI in the financial context and its specific applications in AML monitoring systems are revealed. The evolution from an instrumental understanding of computer programs to the recognition of the special status of autonomous decision-making systems is traced. It is established that AI’s ability to self-learn and form unpredictable conclusions creates new legal challenges, particularly regarding the attribution of responsibility, which are resolved through the distribution of obligations between technology developers and users.International approaches to AI regulation in the AML/CFT sphere are analyzed. FATF recommendations that establish risk-based approach principles are examined. The European model based on the EU AI Act, which came into force on August 1, 2024, and classified AML systems as high-risk, is studied. The American model, characterized by flexibility through Financial Crimes Enforcement Network (FinCEN) initiatives, as well as regional practices, including initiatives by the Monetary Authority of Singapore and the Financial Conduct Authority of the United Kingdom, is characterized. Two dominant approaches are identified: the European (comprehensive and normatively detailed) and the American (more adaptive and practically oriented). It is concluded that the key problem remains the lack of international harmonization of legal standards, which creates fragmentation of the regulatory environment and complicates operations conducted by transnational financial institutions. The rationale for establishing unified principles at the global level through the activities of international organizations is argued, which will allow ensuring a balance between innovation and legal certainty in the field of AI application. Proposals for improving the legislative regulation of this sphere in Ukraine are substantiated, taking into account European standards and contemporary technological challenges.